Children’s lead poisoning in the industrial upper Silesian Region of Poland - Stęplewski, Zygmunt (Polish Journal of Public Health, 2010)
This review presents results of Polish – American collaborative program performed by us and Dr. Robert W  Rider of Yale University as a representative of Physicians for Social Responsibility. The present problems of lead poisoning in children are also presented. The main risk factors in lead poisoning in Upper Silesian region of Poland were established in a case control study. Main risk factors influencing lead poisoning in children are presented according to their strength of infl uence. From highest to the lowest, the risk factors were: mother’s level of education; the age of the dwelling occupied by child’s family; drinking of tap water; orientation of child’s room window (dirty Or clean area); mean home dust lead concentration and father’s educational level. The main risk factors are related to the family life style, factors clearly susceptible to the preventive measures such as education and change of hygienic habits